Modelo de previs\~ao para o PIB da agropecuária utilizando um método bottom-up - Pedro Mendes Garcia; José Ronaldo de Castro Souza Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study introduces and evaluates a bottom-up methodology for projecting the Gross Value-Added of the agricultural sector (agricultural GDP). This approach integrates econometric methods with early crop forecasts, which are released one year ahead of annual production figures by specialized agencies, such as the Brazilian Institute of Geography and Statistics (IBGE). The methodology not only allows for a detailed analysis of trends in the sector's value-added but also produces projections that are consistent with the sector's production forecasts and are more adept at anticipating trend changes than purely econometric methods. Statistical tests conducted confirm the efficacy of the proposed method, demonstrating its superior accuracy in forecasting agricultural GDP compared to market expectations outlined in the Focus Bulletin of the Central Bank of Brazil, particularly during years marked by significant fluctuations in sector performance.
Keywords: Q11; E32; E37; 330; Agricultural GDP; GDP forecasts; forecasting models